2011
DOI: 10.1111/j.1475-3588.2011.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction in the island of Hippocrates: the associations between internet abuse and adolescent off‐line behaviours

Abstract: Background:  To investigate the phenomenon of internet addiction and concurrent social (off‐line) behaviours of an adolescent population a cross‐sectional survey of the entire adolescent student population (N = 1270, aged 14–18) of the island of Kos in Greece was conducted.Method:  Completion by the survey participants of a demographic questionnaire, the 8‐question YDQ (Diagnostic Questionnaire for Internet Addiction) and the 20‐question IAT (Internet Addiction Test), followed by comparative analysis between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 39 publications
3
20
0
5
Order By: Relevance
“…The sample sizes ranged from 1,270 in Greece [71,72] to 10,988 adolescents and young adults in China, aged 13-23 years [78] The same cut-off, i.e., endorsing a minimum of five out of eight diagnostic items, has been applied to a majority of these studies. Internet addiction prevalence rates ranged from 1.7% of boys and 1.4% of girls in a representative sample of Finnish adolescents [77] to 26.4% and 26.7% at wave one and wave two in a longitudinal sample of adolescent students in Hong Kong, respectively [73].…”
Section: Prevalence Of Internet Addiction In Adolescentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample sizes ranged from 1,270 in Greece [71,72] to 10,988 adolescents and young adults in China, aged 13-23 years [78] The same cut-off, i.e., endorsing a minimum of five out of eight diagnostic items, has been applied to a majority of these studies. Internet addiction prevalence rates ranged from 1.7% of boys and 1.4% of girls in a representative sample of Finnish adolescents [77] to 26.4% and 26.7% at wave one and wave two in a longitudinal sample of adolescent students in Hong Kong, respectively [73].…”
Section: Prevalence Of Internet Addiction In Adolescentsmentioning
confidence: 99%
“…In eleven studies, the IADQ [13] was used to assess Internet addiction in adolescents [68][69][70][71][72][73][74][75][76][77][78]. The sample sizes ranged from 1,270 in Greece [71,72] to 10,988 adolescents and young adults in China, aged 13-23 years [78] The same cut-off, i.e., endorsing a minimum of five out of eight diagnostic items, has been applied to a majority of these studies.…”
Section: Prevalence Of Internet Addiction In Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is through the score on a specific scale: for example, it is diagnosed in subjects with five of the eight diagnostic criteria on the YDQ 34,40,44,47,52,64,65 ; or on the CIAS, it is diagnosed with a minimum score of 63/64. 35,37,41,48,59 A second approach would be to extract categories using percentiles (P), such as the 75 P 24 or 95 P…”
mentioning
confidence: 99%
“…Previous studies found that aggression behavior could be influenced by many factors, such as personal factors including personality (Luo, 2008;Denson, DeWall, & Finkel, 2012), interpersonal barriers (Ji, Wei, Chen, & Zhang, 2012), biological factors (Wang & Zhang, 2010), etc., family factors including parental rearing styles (Luo, 2008;Lv, Chen, & Wang, 2003), family environment (Lv et al, 2003;Barrett, Rapee, Dadds, & Ryan, 1996;Sijtsema, Oldehinkel, Veenstra, Verhulst, & Ormel, 2014), etc., and social factors including frustration and pressure (Taylor, & Kluemper, 2012;Riley, Watt, Richardson, & De Alwis, 2012), media violence (Fisoun, Floros, Geroukalis, Ioannidi, Farkonas, & Sergentani, 2012;Mehroof & Griffiths, 2010;Polman, De Castro, & Van Aken, 2007) addiction" of the college students is becoming more and more serious. It affects various aspects of college students' study and life (Wang & Li, 2012).…”
Section: Introductionmentioning
confidence: 99%